The Community Satisfaction Index for Local Government Services uses the EVLN Model in the City of Bandung - Mas Halimah; Ramadhan Pancasilawan; Bonti Bonti (Jurnal Manajemen Pelayanan Publik, 2023)
The purpose of this research is to the satisfaction of public service of the local government of Bandung City. This study is also a recent study conducted in Indonesia in a public paradigm. Several public services focus on this research, such as Health, Education, Economy and Development, and Public Service. This Government Service sector still needs to be measured in how to understand the condition of health services delivered. Education is an important aspect in developing countries. In Indonesia, there are still many people who have not received 9 years of education. The central government has instructed free tuition. Then in economic and development problems also researchers see still many people who are unemployed and previously uneven development in some sub-districts close to the center of power with a far from the center of power. For Public Services related to obtaining certain services, for example, if you want to get Public Health Insurance service (JAMKESMAS) then this community must have ID cards and other information. The method used in this study using the quantitative descriptive method with respondents consisting of 50 people community service users. The measure of community satisfaction is by four sectors using the model EVLN (Exit, Voice, Loyalty, and Neglected) from Hirschman. This model has been used in some developed and developing countries to measure job dissatisfaction or non-discrimination of public services in a local government.